Electrochemical Behaviour of Arsenic on Copper Deposition Reaction in the Low Copper Concentration Electrolyte - Chen, Shaohua; Ding, Yi; Zhao, Donglin; Lu, Daorong; Wang, Jiaquan (Asian Journal of Chemistry, 2013)
During the electrolytic refining process of copper, arsenic as a common impurity ions, would affect the deposition reaction of the copper cathodes and thereby affected the quality of the cathode copper. In this paper, linear sweep voltammetry and cyclic voltammetry were used to analyze the electrochemical behaviour of arsenic ion in the low-copper electrolyte system. The effect of arsenic ion impacting the limiting current density in copper deposition, as well as co-deposition reaction mechanism on the cathode copper were also studied, which would provide a theoretical basis on the actual improvements of copper electrolysis process.